Plastic soil covers in vegetative development, production and quality of strawberries - Santin, Anderson; Villa, Fabíola; Paulus, Dalva; Santin, Jonathan; Piva, André Luiz; Mezzalira, Eder Júnior; Ritter, Giovana (Revista Ceres, 2025)
The purpose this study was to evaluate the vegetative development, yield and quality of strawberry cultivars of short and neutral days as a function of soil cover. Two experiments were carried out in a protected environment. The experimental design used in both experiments consisted of randomized blocks, with subdivided plots. Harvests were carried out every two days, when the berries presented 75% of the red coloration of the epidermis, with evaluation of yield, number of fruits/plant, and fresh biomass of the fruits. For fruit quality, the pH, SS, titratable acidity, SS/TA ratio and fruit staining were evaluated. The contents of chlorophyll a and b, chlorophyll a + b and the chlorophyll a/b ratio in the leaves were also measured. At the end of the productive cycle, destructive evaluations of leaf number, leaf area and dry biomass of shoot were carried out. Cultivation on white PSC presented plants with lower vegetative development, higher yield, and fruit size. Among the cultivars of short days, Camino Real presented bigger and more attractive fruits regarding the appearance of color of epidermis. For neutral day cultivars, Aromas obtained higher yield.